Occurrence of dysplasia and adenocarcinoma after experimental chronic ulcerative colitis in hamsters induced by dextran sulphate sodium. Issue 11 (November 1992) - Yamada, M; Ohkusa, T; Okayasu, I
Abstract : In this study, long term dextran sulphate sodium administration was studied to ascertain whether colorectal carcinoma could be produced in patients with long standing ulcerative colitis. Simultaneously, changes in the intestinal microflora were analysed. Low grade to high grade dysplasia was seen in three of the five hamsters treated with 1% dextran sulphate sodium solution for 100 days, while no dysplasia was detected in the eight animals concomitantly treated with metronidazole, an antianerobic microbial agent, which prevents colonic ulceration. In these two groups, none of the animals developed colorectal cancer over 100 day period. In a group treated for 180 days, seven of the eight animals had dysplasia, and one had two adenomas. Furthermore, four of the eight animals had adenocarcinoma in the transverse colon; they were protruding well differentiated adenocarcinoma in one and non-protruding lesions infiltrating into the musclaris propria in three. The three non-protruding infiltrating adenocarcinomas were classified to be well differentiated adenocarcinoma in one and mucinous adenocarcinoma in two, resembling the type of cancer which complicates ulcerative colitis in man.